Ferroelectric Control of Anisotropic Magnetoresistance in Ultrathin Sr2IrO4 Films toward 2D Metallic Limit - Yuanyuan Zhang; Qiuchen Wu; Yifei Hao; Xia Hong (Advanced Physics Research)
Abstract The Ruddlesden‐Popper 5d iridate Sr2IrO4 is an antiferromagnetic Mott insulator with the electronic, magnetic, and structural properties highly intertwined. Voltage control of its magnetic state is of intense fundmenatal and technological interest but remains to be demonstrated. Here, the tuning of magnetotransport properties in 5.2 nm Sr2IrO4 via interfacial ferroelectric PbZr0.2Ti0.8O3 is reported. The conductance of the epitaxial PbZr0.2Ti0.8O3/Sr2IrO4 heterostructure exhibits ln(T) behavior that is characteristic of 2D correlated metal, in sharp contrast to the thermally activated behavior followed by 3D variable range hopping observed in single‐layer Sr2IrO4 films. Switching PbZr0.2Ti0.8O3 polarization induces nonvolatile, reversible resistance modulation in Sr2IrO4. At low temperatures, the in‐plane magnetoresisance in the heterostructure transitions from positive to negative at high magnetic fields, opposite to the field dependence in single‐layer Sr2IrO4. In the polarization down state, the out‐of‐plane anisotropic magnetoresistance RAMR exhibits sinusoidal angular dependence, with a 90° phase shift below 20 K. For the polarization up state, unusual multi‐level resistance pinning appears in RAMR below 30 K, pointing to enhanced magnetocrystalline anisotropy. The work sheds new light on the intriguing interplay of interface lattice coupling, charge doping, magnetoelastic effect, and possible incipient ferromagnetism in Sr2IrO4, facilitating the functional design of its electronic and material properties.